2016
DOI: 10.4103/0253-7613.182882
|View full text |Cite
|
Sign up to set email alerts
|

The effects of tramadol on hepatic ischemia/reperfusion injury in rats

Abstract: Objectives:Tramadol is a centrally acting synthetic analgesic. It has a cardioprotective effect against myocardial ischemia-reperfusion (I/R) injury in isolated rat heart. We hypothesized that tramadol may exert a similar protective effect on hepatic I/R injury. Hence, the current investigation was designed to study the possible protective effects of tramadol on experimentally-induced hepatic I/R injury in rats.Materials and Methods:Tramadol was administered 30 min before ischemia following which the rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Thereby, some evidences suggest that peripheral actions of tramadol involve increasing in antioxidant defenses. Mahmoud et al 20 , showed the use of this substance reduced oxidative by means of glutathione peroxidase overexpression and decreasing in MDA formation. On the same way, Takhtfooladi et al 21 observed increasing in catalase and superoxide dismutase in skeletal muscle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Thereby, some evidences suggest that peripheral actions of tramadol involve increasing in antioxidant defenses. Mahmoud et al 20 , showed the use of this substance reduced oxidative by means of glutathione peroxidase overexpression and decreasing in MDA formation. On the same way, Takhtfooladi et al 21 observed increasing in catalase and superoxide dismutase in skeletal muscle.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Serum and tissue MDA levels in ischemia-reperfusion rats were significantly increased. The muscle tissue GSH, SOD, and CAT levels in the Ischemia-reperfusion group were significantly lower than the control group [52].…”
Section: The Antioxidant Effects Of Tramadol On Ischemia-reperfusion ...mentioning
confidence: 70%
“…It also increased IL-10 levels in hepatic tissues. TR reduced oxidative stress parameters except for SOD activity [52].…”
Section: The Antioxidant Effects Of Tramadol On Ischemia-reperfusion ...mentioning
confidence: 93%
See 1 more Smart Citation
“…It inhibits reuptake of noradrenaline and serotonin (5HT) 13 . Tramadol is a synthetic drug with cardio-protective and hepatoprotective effect 14 . Metabolism of tramadol occurs in the liver 15 .…”
Section: Introductionmentioning
confidence: 99%